Chronic antigen stimulation in melanoma induces T cell exhaustion and limits efficacy of T cell bispecific therapies - Idil Hutter-Karakoc; Eleni Maria Varypataki; Aparna Neelakandhan; Simone Lang; Vesna Kramar; Ahmet Varol; Sasha Simons; Marine Richard; Mudita Pincha; Dario Venetz; Johannes Sam; Nicole Joller; et al. (OncoImmunology)
T cell bispecific antibodies (TCBs) have demonstrated promising results in patients with solid tumors, yet the immunological mechanisms influencing their efficacy require further investigation. T cell exhaustion, induced by prolonged antigen exposure, is known to compromise T cell-based immunotherapies, but its effect on TCB efficacy remains unclear. Herein, we assessed the TCB efficacy on tumor-specific T cells, emphasizing their functional status. Utilizing an immunocompetent mouse model with melanoma expressing an immunogenic antigen, we showed that tumor-specific T cells acquire an exhausted phenotype and fail to expand under TCB treatment. Both mouse and human tumor-specific T cells in vitro demonstrated that chronically stimulated T cells exhibit a reduced response to TCBs. The comparison of TCB efficacy in T cell-inflamed versus non-inflamed tumors in mice revealed TCB success depends more on T cell functional fitness than their initial abundance. These data underscore the importance of T cell exhaustion, suggesting that exhausted tumor-specific T cells are unlikely to be the primary effectors redirected by TCBs for tumor eradication. Our study highlights the need to maintain T cell fitness and prevent exhaustion to enhance TCB therapy outcomes, which may help identify patients who could benefit most from TCB treatments in clinics.